PENGARUH KEPEMILIKAN MANAGERIAL DAN ARUS KAS BEBAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI - Perwira, Hendrik; Agoes, Sukrisno; Indrajati, MF Djeni (Jurnal Kontemporer Akuntansi, 2025)
The delegation of authority from shareholders as principal to management as agent causes agency conflict to arise between shareholders and managers. Agency conflict needs to be minimized in various ways so that the company's objection in maximize the value of the company can be achieved. This study aims to empirically examine the effect of managerial ownership and free cash flow on firm value with dividend policy as a moderating variable. This study uses panel data regression on 55 companies listed on the Indonesia Stock Exchange and IDX80 in the 2019-2021 period. The dependent variable in this study is firm value. The independent variables in this study are managerial ownership and free cash flow. The moderating variable in this study is dividend policy. The results of this study indicate that Managerial Ownership has a positive effect on firm value. Furthermore, Free Cash Flow has no effect on firm value. Dividend policy does not strengthen the effect of managerial ownership and free cash flow on firm value.